The Effect of Manure‐Based Fertilisers on Nitrogen Mineralisation and Greenhouse Gases Emissions After Soil Application - Joana Prado; Erik Meers; Henrique Ribeiro; Paula Alvarenga; David Fangueiro (Journal of Sustainable Agriculture and Environment, 2025)
ABSTRACT The continuous increase of costs with mineral fertilisers made farmers search for alternatives, while livestock producers face strong challenges to, sustainably, manage large amount of manure. It is, therefore, important to provide strategies that could enhance the use of manures in agriculture, recycling nutrients and organic matter. This study aimed to evaluate the use of manure‐based fertilisers (MBFs), with tailored N:P2O5 ratios, to values commonly used by farmers: 1:1, 2:1 and 0.5:1. These MBFs were applied to a sandy soil and the resulting nitrogen mineralisation, nitrification rates and greenhouse gases emission were measured. Raw manures (cattle slurry [CaS], pig slurry [PiS] and poultry manure [PoM]) were used directly to obtain the 1:1 N:P2O5 ratio. For the 2:1 ratio, two MBFs were produced with each raw manure, plus the addition of urea or ammonium sulphate to provide additional N. To prepare the P richer fertiliser with a 0.5:1 ratio, the pig slurry solid fraction was used on its own, while the CaS and PoM were blended with superphosphate (SP) or with phosphoric acid, to provide additional P. In the 1:1 ratio, both slurries had higher mineralisation rates (~35% of the organic N applied) and lower environmental impact, compared with PoM. Blending PoM with urea, for the 2:1 ratio, improved the N mineralisation rate, while decreasing the N2O and CO2 emissions to almost half the value observed with the raw PoM, enhancing its fertiliser value. The addition of SP to PoM decreased the N2O emissions and presented a similar nitrification rate as the raw material. The results demonstrate that it is possible to produce MBFs with these specific N:P2O5 ratios, with potential agronomical and environmental benefits, compared with the raw material.